Evaluating the impact a proposed family planning model would have on maternal and infant mortality in Afghanistan. (23rd September 2013) - Rahmani, Ahmad Masoud; Wade, Benjamin; Riley, William
Summary Objective This study aimed to assess the potential impact a proposed family planning model would have on reducing maternal and infant mortality in Afghanistan. Background Afghanistan has a high total fertility rate, high infant mortality rate, and high maternal mortality rate. Afghanistan also has tremendous socio‐cultural barriers to and misconceptions about family planning services. Methods We applied predictive statistical models to a proposed family planning model for Afghanistan to better understand the impact increased family planning can have on Afghanistan's maternal mortality rate and infant mortality rate. We further developed a sensitivity analysis that illustrates the number of maternal and infant deaths that can be averted over 5 years according to different increases in contraceptive prevalence rates. Results Incrementally increasing contraceptive prevalence rates in Afghanistan from 10% to 60% over the course of 5 years could prevent 11 653 maternal deaths and 317 084 infant deaths, a total of 328 737 maternal and infant deaths averted. Conclusion Achieving goals in reducing maternal and infant mortality rates in Afghanistan requires a culturally relevant approach to family planning that will be supported by the population. The family planning model for Afghanistan presents such a solution and holds the potential to prevent hundreds of thousands of deaths. Copyright © 2013 John Wiley & Sons, Ltd.